Regulating the Electricity Industry - Chen, Zhenyu (Université d'Ottawa | University of Ottawa, 2012)
This paper reviews some of the major insights of the economics literature regarding regulation of the electricity industry. We start with a brief review of the theory of natural monopoly. Then, as the most popular pricing method, peak-load pricing is assessed for the U.S. and Chile. Next, the three most commonly used regulation methods in the electricity industry are reviewed and the problems of these regulation methods are summarized. Ramsey-pricing regulation is subject to a series of unrealistic assumptions and highly depends on the availability of good information about price elasticity. Price-cap regulation, on the other hand, is subject to quality issues. Rate of return regulation has a negative impact on innovation. The paper further discusses the supply quality (reliability) issue. The impact of different regulation methods on welfare is reviewed. Lastly, the relationship between investment and market power is addressed in detail.